Analysis of Lighting Electromagnetic Field on Numerical Terrain and Urban Model using Three‐Dimensional MW‐FDTD Parallel Computation - OIKAWA, TAKASHI; SONODA, JUN; HONMA, NORIYASU; SATO, MOTOYUKI (Electronics and communications in Japan, 2017)
SUMMARY Analysis of lightning electromagnetic field using the finite‐difference time‐domain (FDTD) method has been studies in recent year. However, large‐scale analysis on real environment has not been considered, because the FDTD method requires huge computational cost on large‐scale analysis. We proposed a three‐dimensional moving window FDTD (MW‐FDTD) with parallel computation and applied to large‐scale analysis of lightning electromagnetic field with a real numerical terrain model. In this paper, we have studied about large‐scale analysis of lightning electromagnetic field with real urban models considering many buildings using our MW‐FDTD with parallel computation. We have shown effects of observed electromagnetic field on urban model.